Fraudulent Financial Reporting dianalisis dengan Fraud Pentagon Pada Perusahaan Perbankan yang listing di BEI Tahun 2017-2019 - Tatas Ridho Nugroho; Hari Setiono; Khurniatul Irsyadah (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2021)
The meaning of financial statements is important information for management and stakeholders, so the standards that must be met by financial statements are to have reliable nature and representation faithfulness. However, sometimes financial statements are presented containing fraud in them so that they cannot be used as a basis for decision making. Observations intend to determine the effect of the theory of fraud pentagon which includes financial targets, financial stability, external pressure, ineffective monitoring, change in auditors, change of directors and dualism position on fraudulent financial reporting. This observation is quantitative. The population is all banking companies on the 2017-2019 BEI. Samples were taken through purposive sampling obtained 24 companies. Secondary data in the form of annual reports and financial reports were analyzed through multiple linear regression analysis. Observations show that financial stability, external pressure and change of directors affect fraudulent financial reporting. Meanwhile, financial targets, ineffective monitoring, change in auditors and dualism position do not affect fraudulent financial reporting. Simultaneously, these observations show that financial target variables, financial stability, external pressure, ineffective monitoring, change in auditors, change of directors and dualism position affect fraudulent financial reporting